Crescimento e produção de rúcula (Eruca Sativa L.) em função dos espaçamentos e da época de cultivo - Gonçalves, Edilaine Della Valentina (2013)
With the goal of providing informations on the best growing season and the best spacing between plants and rows, and in order to achieve higher return and quality of arugula cv. Bella, two experiments were led in Unioeste Marechal Cândido Rondon PR. The first experiment was performed in spring 2011 and autumn and winter 2012, aiming of evaluate arugula‟s growth. The second experiment was realized over spring 2011 and summer, autumn and winter 2012, evaluating the productive performance of arugula‟s plant. The experimental delineation used was a randomized block with four replications in a 3x2 factorial arrangement. The first factor was consisted of three spacings‟ row (0.20, 0.25 and 0.30 m) and the second factor was consisted of two spacings between the plants (0.05 and 0.10 m). The cultivar used was Bella arugula. The first experiment: the highest value of leaf area and total leaf dry mass were obtained in the spring and winter seasons with spacing between row of 0.25 and 0.30 m and between plant‟s spacing of 0.10 m, so that on crops of autumn and winter seasons there was only seasonal effect to this feature. The specific leaf area was higher in spacing of plants with 0.10 m in the springtime, so that in autumn and winter there was only seasonal effect and obtained greater value for the variable in autumn. The absolute growth rate was influenced only by the spring season. In the autumn was verified effect of plants‟ spacings, with highest value of 0.10 m. During the winter crop there was effect of row spacings of 0.25 and 0.30 m and between plants of 0.10 m. These treatments have obtained better returns. About the relative growth rate there was effect in the spring and winter. The best results were obtained for the row spacing of 0.20 and 0.30 m during the autumn and presented a significant effect in plants of 0.10 m. Concerning the rate of net assimilation there was seasonal effect of the seasons of autumn and spring, with the greatest rate values obtained in autumn. The highest growth rate was obtained in plant spacing of 0.10 m. The sencond experiment: there was seasonal effect in plants‟ height, so that was verified taller plants in the spring and winter with values that did not differ statistically. The diameter of plants was higher in the winter, differing from the other seasons. The largest leaf area was noticed during the spring. The taller plants were found in plants‟ spacing of 0.05 m whose values differ from those verified in the spacing of 0.10 m. There was no difference in leaf area and diameter for different spacings. There was no difference in leaf area and diameter of plants for different plants‟ spacing. With regard to the row spacing was not found statistically significant differences for leaf area, leaf number and diameter plants. The unfolding of the interaction between seasons and spacings revealed that the highest number of leaves and total leaf fresh weight was obtained in plant spacing of 0.10 m and in the unfolding spacings in seasons, the highest average were obtained in the spring. Regarding productivity, the unfolding in spacings showed that the greater productivity in the spring, summer and winter was obtained in the spacing of 0.20 m, while the better cultivation spacing was 0.25 m in autumn. Unfolding the spacings in seasons, the best productivity results were obtained in the spring. The greatest productivity of arugula‟s cultivation was obtained in plants‟ spacings of 0.05 m